Case Report: Two New Cases of Chromosome 12q14 Deletions and Review of the Literature - Deng, Ruizhi; McCalman, Melysia T.; Bossuyt, Thomas P.; Barakat, Tahsin Stefan (Frontiers in Genetics, 2021)
Interstitial deletions on the long arm of chromosome 12 (12q deletions) are rare, and are associated with intellectual disability, developmental delay, failure to thrive and congenital anomalies. The precise genotype-phenotype correlations of different deletions has not been completely resolved. Ascertaining individuals with overlapping deletions and complex phenotypes may help to identify causative genes and improve understanding of 12q deletion syndromes. We here describe two individuals with non-overlapping 12q14 deletions encountered at our clinical genetics outpatient clinic and perform a review of all previously published interstitial 12q deletions to further delineate genotype-phenotype correlations. Both individuals presented with a neurodevelopmental disorder with various degrees of intellectual disability, failure to thrive and dysmorphic features. Previously, larger deletions overlapping large parts of the deletions encountered in both individuals have been described. Whereas individual 1 seems to fit into the previously described phenotypic spectrum of the 12q14 microdeletion syndrome, individual 2 displays more severe neurological symptoms, which are likely caused by haploinsufficiency of the BAF complex member SMARCC2, which is included in the deletion. We furthermore perform a review of all previously published interstitial 12q deletions which we found to cluster amongst 5 regions on chromosome 12, to further delineate genotype-phenotype correlations, and we discuss likely disease relevant genes for each of these deletion clusters. Together, this expands knowledge on deletions on chromosome 12q which might facilitate patient counseling. Also, it illustrates that re-analysis of previously described microdeletions syndromes in the next generation sequencing era can be useful to delineate genotype-phenotype correlations and identify disease relevant genes in individuals with neurodevelopmental disorders.